Synthesis of Zwitterionic Lipidoids and its Biomedical Applications - Li, Prudence. (2018)
Abstract: Developing drug delivery systems that can efficiently and effectively release therapeutic payload without inducing side effects has proved to be a difficult task. This is why it is becoming increasingly important to be able to synthesize tunable drug carriers where their physical and chemical properties can be specific to the targeted application. Zwitterionic lipidoids are an emerging new class of lipid-like material that have neutral charge. Many studies have cited zwitterionic lipidoids to exhibit excellent stability and low cytotoxicity due to their unique structures. As result, they play a key role in advancing drug nanotechnology. Thus, it is critical to expand the combinatorial library of synthesized zwitterionic lipidoids. By conjugating different polar heads groups with hexadecyl acrylate, new zwitterionic lipidoids were developed. Although amino acid based zwitterionic lipidoids have been studied in literature, the particular use of β-alanine as a head group has not been done. Its resulting zwitterionic lipidoid produced significantly lower cytotoxicity in comparison to current literature and makes this a novel approach to drug delivery. Their properties were then evaluated and their biomedical applications investigated.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Qiaobing Xu.; Committee: Xiaocheng Jiang, and Samuel Thomas.; Keyword: Biomedical engineering.